Carbon Footprint Reduction Strategy at Kompas Gramedia - Asnil Bambani Amri; Eliana Sari; Ahman Sya; Dian Alfia Purwandari (Eduvest - Journal of Universal Studies, 2026)
Studies related to carbon emission reduction in business entities have been mostly conducted in the manufacturing, transportation, and energy sectors. Internal strategies for reducing carbon footprints in the media industry are still relatively limited, particularly in developing countries, including Indonesia. This research aims to analyze the carbon footprint reduction strategies formulated and implemented by Kompas Gramedia (KG) Media, an integrated media company, which positions media as a business focus that simultaneously acts as an emissions producer and an agent for shaping public awareness. The research employed a qualitative approach with a case study design. Data were obtained through in-depth interviews with strategic company actors, followed by analysis of policy documents and observations of operational practices. The analysis was conducted thematically, referring to Fred R. David's strategic management framework (strategy formulation, implementation, and evaluation) and linked to the concept of corporate sustainability and carbon footprint management based on the Greenhouse Gas Protocol. The results of this study indicate that the carbon footprint reduction strategy implemented at KG Media is not only oriented towards operational technical efficiency, but is integrated with the transformation of the media business model through digitalization, sustainability governance, and the formation of a low-carbon organizational culture. The novelty of this study lies in mapping carbon reduction strategies in the media industry as a non-manufacturing sector, as well as in the finding that the integration of internal strategies and media educational functions strengthens the effectiveness of corporate sustainability.